Impact of single parenting on the development of the girl-child in Warri South West Local Government Area of Delta State, Nigeria - Yesufu, Sumaina; Boyi, Marian Weyinmi (NIU Journal of Social Sciences, 2024)
Prior to this time, single parents in Nigeria were either unheard of or were treated as exceptional occurrences. Currently, single parenting is gradually becoming a norm. The proportion of children in single-parent families, especially girls, is on the increase. The rise in single parent families, particularly those with mothers and young children, may be related to a social value shift away from stable marriages toward divorce and spousal death. The objective of this study was to examine the impact of single parenting on the development of the girl child in Warri South West Local Government Area of Delta State , Nigeria. The study adopted the survey design using quantitative procedure to gather responses from 400 research participants. The data was analyzed with the aid of simple percentage and chi-square. The results show that single parenting has significant effect on the emotional development of the girl child. The result further revealed that there is significant relationship between single parenting and girl-child academic performance. It is recommended that single mothers should encourage their girl-child to be serious with their academic activities in school. Key Words : Academic performance, emotional development, single parenting, marriage, separation, the girl-child